The productivity of strategies: an analysis of the Pacaembu concession, São Paulo, Brazil - Stela de Camargo Da Dalt (Geografares, 2022)
The article analyzes the concession of the Pacaembu sports complex to the private sector, started in the 1990s, in order to evaluate the lessons learned from studies, discussions and projects developed (and not concluded) during the municipal administrations of Paulo Maluf (1993-1996), Celso Pitta (1997-1999), José Serra and Gilberto Kassab (2005-2008), Gilberto Kassab (2009-2012) and Fernando Haddad (2013-2016). The focal point of our investigation is the concession of Pacaembu as a political, social, economic and legal phenomenon. Our main objective is to understand the network of agents and actors involved and the productivity of this conflict. To carry out this analysis, we will focus on the accumulation generated by successive attempts and the “innovations” — or strategies — formulated by João Doria and Bruno Covas’ government (PSDB/2017-2020) designed to unlock the concession. Observing the strategies and their results, we will consider their effectiveness in producing a reality desired by the municipality: the reduction of the State, also called privatization.
Keywords: Pacaembu; concession; privatization; sports complex